Analysis of potential tourism development in perintis reservoir by using environmental approach, Suwawa, Bone Bolango - Audrey Maura; Meliana Putri Suman; Salsabilah Hamidah Putri Wicaksono; Anna Pudianti; Vincentia Reni Vitasurya; David Chow (Regional Development Information Center, Universitas Sebelas Maret, 2025)
Perintis Reservoir has big potential with its amazing view, water coverage, and decent nature. However, the reservoir tends to be temporarily crowded by visitor when there is national event that held by government. Moreover, the majority of visitor is only local people. The objective of this study is to create a recommendation and guideline to enhance the future development of Perintis reservoir, so it can be regularly visited by local people, national tourist, and even international tourist. This study method employed various approaches, such as literature review, quantitative data collection, and observation. The identified problem in observation and data collection were solved by literature review. Research results show that there are some problems need to be solved such as inconvenient thermal conditions because of tropical climate and inadequate shading, unready urban facility, unorganized MSME, lack of walkability for pedestrians, and desolate tourism destinations. The environmental approach was chosen as the main solution because it’s the most suitable. The improvement of sidewalk, people domination rather than vehicle, and adding forest bathing sensation by planting wide-crown tree is needed. The Riparian buffer system and rain garden can help to balance water conservation while increasing the naturalness of the landscape. Cycling and other physical activities have a correlation with walkability and should be emphasized. Social physical activities and MSME’s integration with nutrition in wellness tourism themes can be a Perintis reservoir branding.